Transfer of Maternal Antimicrobial Immunity to HIV-Exposed Uninfected Newborns - Abu-Raya, Bahaa; Smolen, Kinga K.; Willems, Fabienne; Kollmann, Tobias R.; Marchant, Arnaud (Frontiers in Immunology, 2016)
The transfer of maternal immune factors to the newborn is critical for protection from infectious disease in early life. Maternally acquired passive immunity provides protection until the infant is beyond early life’s increased susceptibility to severe infections, or until active immunity is achieved following infant’s primary immunization. However, as reviewed here, HIV infection alters the transfer of immune factors from HIV-infected mothers to the HIV-exposed newborns and young infants. This may relate to the immune activation in HIV-infected pregnant women, associated with the production of inflammatory cytokines at the materno-fetal interface associated with inflammatory responses in the newborn. We also summarize mother-targeting interventions to improve the health of infants born to HIV-infected women such as immunization during pregnancy and reduction of maternal inflammation. Maternal immunization offers the potential to compensate for the decreased transplacentally transferred maternal antibodies observed in HIV-exposed infants. Current data suggest reduced immunogenicity of vaccines in HIV-infected pregnant women, possibly reducing the protective impact of maternal immunization for HIV-exposed infants. Fortunately, levels of antibodies appear preserved in the breast milk of HIV-infected women, which supports the recommendation to breastfeed during antiretroviral treatment to protect HIV-exposed infants.